Silicon matrix technique for the restoration of the crown fracture and mouthguard for prevention of injuries - Quintana del Solar, Carmen Inocencia (2010)
The non-complicated fractures of the crown constitute one of the frequent dentoalveolar trauma in the permanent teething. The most vulnerable tooth is the upper central incisor, which occurs in the majority of the dental traumatic injuries. Depending on the extent of the crown fractures, there are different options of restoring treatments. This clinical case shows: The stratified technique of resin combined with the silicone matrix Achieving highly esthetic results in a more brief pediatric dentistry appointment. Moreover, because the patient shows risk factors for dental trauma it was decided to make a mouthguard to prevent future dentoalveolar trauma and to get a greater life time for the restoration.